Trail running injury risk factors: a living systematic review. Issue 10 (12th January 2022) - Viljoen, Carel; Janse van Rensburg, Dina C (Christa); van Mechelen, Willem; Verhagen, Evert; Silva, Bruno; Scheer, Volker; Besomi, Manuela; Gajardo-Burgos, Rubén; Matos, Sérgio; Schoeman, Marlene; Jansen van Rensburg, Audrey; van Dyk, Nicol; et al.
Abstract : Objective: To review and frequently update the available evidence on injury risk factors and epidemiology of injury in trail running. Design: Living systematic review. Updated searches will be done every 6 months for a minimum period of 5 years. Data sources: Eight electronic databases were searched from inception to 18 March 2021. Eligibility criteria: Studies that investigated injury risk factors and/or reported the epidemiology of injury in trail running. Results: Nineteen eligible studies were included, of which 10 studies investigated injury risk factors among 2 785 participants. Significant intrinsic factors associated with injury are: more running experience, level A runner and higher total propensity to sports accident questionnaire (PAD-22) score. Previous history of cramping and postrace biomarkers of muscle damage is associated with cramping. Younger age and low skin phototypes are associated with sunburn. Significant extrinsic factors associated with injury are neglecting warm-up, no specialised running plan, training on asphalt, double training sessions per day and physical labour occupations. A slower race finishing time is associated with cramping, while more than 3 hours of training per day, shade as the primary mode of sun protection and being single are associated with sunburn. An injury incidence range 0.7–61.2 injuries/1000 hours of running and prevalence range 1.3% to 90% were reported. The lower limb was the most reported region of injury, specifically involving blisters of the foot/toe. Conclusion: Limited studies investigated injury risk factors in trail running. Our review found eight intrinsic and nine extrinsic injury risk factors. This review highlighted areas for future research that may aid in designing injury risk management strategies for safer trail running participation. PROSPERO registration number CRD42021240832.